Effects of Transcatheter Arterial Embolization for Chronic Intractable Shoulder Pain: A Prospective Clinical Study - Kun Yung Kim; Young-Min Han; Myoung-Hwan Ko; Jeong-Hwan Seo; Sung-Hee Park; Yu Hui Won; Gi-Wook Kim (International Journal of Clinical Practice)
Trial Registration: Korean Registry of Clinical Trials: KCT0004720